Microcystins in New Zealand: a review of occurrence, congener diversity and cell quotas. Issue 2 (3rd April 2019) - Puddick, Jonathan; Thomson-Laing, Georgia; Wood, Susanna A.
ABSTRACT: Microcystin, a common class of cyanobacterial toxin, was first detected in New Zealand in 1997. Subsequent research has demonstrated that microcystins are widely distributed around New Zealand and are commonly detected in planktonic samples from lakes and reservoirs. Microcystis is the predominant microcystin-producing cyanobacteria reported in New Zealand and two different microcystin congener profiles have been detected in the majority of samples tested. Benthic species of Planktothrix and Nostoc have also been confirmed as microcystin producers. Whilst the Planktothrix is infrequently observed, Nostoc is common in lakes, rivers and terrestrial environments. However, there is relatively little information on microcystin congener diversity or the distribution of microcystin-producing Nostoc in New Zealand. To-date, genome sequencing and analysis has only been conducted on one New Zealand cyanobacterium ( Planktothrix CAWBG59). Further genome sequencing of New Zealand microcystin-producing cyanobacteria could provide valuable insights into the genetic controls for microcystin production. There was a high level of inter-strain variability in microcystin cell quotas from Microcystis, highlighting the need for regional analyses to be conducted for risk assessments. Research on the ecological impact of microcystins is limited but shows the toxin can accumulate in New Zealand aquatic organisms, and, when microcystin concentrations are sufficiently high, have negative effects on survival and behaviour.